Translating the Eternal Feminine: Portraits of the Artist in Alexandre Vialatte’s Battling le ténébreux - Frances Egan (Essays in French Literature and Culture, 2019)
In Alexandre Vialatte’s 1928 novel, Battling le ténébreux , a young man projects his quest for self upon a mysterious woman. The character Erna Schnorr incarnates the eternal feminine – a vision of woman constructed for the male hero’s self-realisation. But, penned by a writer-translator amid the modernist crisis of the self, Erna inhabits a strange space between French and German languages and literatures. There, she possesses agency as artist and destabilises the male gaze. This essay first presents protagonist Battling’s series of fantasies as an allegory for a transnational self of the interwar period. And, second, it examines Erna as a subject in translation. I suggest that a translational reading can problematise reductive identities to bring woman back down to earth from the feminine ideal.